Photometric Reductions of Asteroids to the Standard Magnitude System. - Lorenzen, Kayla (My University, 2009)
This study discusses procedures for reducing filtered measurements of asteroids to standard Johnson-Cousins R and V magnitudes. Four asteroids were observed in 2007 and 2008 using Bessel R and V filters.
Color poster with text, images, and graphs.
Keywords: Astronomical photometry; Asteroids--Magnitudes; Posters